Challenges Regarding Network Neutrality for Commercial Deployment of 5G Networks - Izydorek, Szymon; Tadayoni, Reza (Nordic and Baltic Journal of Information & Communications Technologies, 2022)
The paper aims to analyze the impact of equal data treatment applied in the European Union (EU) on the commercial deployment of the upcoming wireless standards such as 5G and beyond. The analysis of the different network neutrality involves several aspects, including engineering, social, economic and political aspects. Considering recent advancements in wireless networks like Network Function Virtualization or Network Slicing, this opens new research possibilities to analyze how various models influence aspects like the profitability of modern standards. To perform the study, a broad literature review and five interviews with the stakeholders from the industry have been done. Then, the knowledge has been segmented and interpreted so that an analysis of the net neutrality on future wireless standards has been given.